The Immediate Effects of Upper Thoracic Translatoric Spinal Manipulation on Cervical Pain and Range of Motion: A Randomized Clinical Trial - Krauss, John (Journal of Manual & Manipulative Therapy, Inc., 2008)
This study examined the effect of translatoric spinal manipulation (TSM) on cervical pain and cervical active motion restriction when applied to upper thoracic (T1-T4) segments. Active cervical rotation range of motion was measured re- and post-intervention with a cervical inclinometer (CROM), and cervical pain status was monitored before and after manipulation with a Faces Pain Scale. Study participants included a sample of convenience that included 32 patients referred to physical therapy with complaints of pain in the mid-cervical region and restricted active cervical rotation. Twenty-two patients were randomly assigned to the experimental group and ten were assigned to the control group. Pre- and post-intervention cervical range of motion and pain scale measurements were taken by a physical therapist assistant who was blinded to group assignment. The experimental group received TSM to hypomobile upper thoracic segments. The control group received no intervention. Paired t-tests were used to analyze within-group changes in cervical rotation and pain, and a 2-way repeated-measure ANOVA was used to analyze between-group differences in cervical rotation and pain. Significance was accepted at p = 0.05. Significant changes that exceeded the MDC(95) were detected for cervical rotation both within group and between groups with the TSM group demonstrating increased mean (SD) in right rotation of 8.23° (7.41°) and left rotation of 7.09° (5.83°). Pain levels perceived during post-intervention cervical rotation showed significant improvement during right rotation for patients experiencing pain during bilateral rotation only (p=.05). This study supports the hypothesis that spinal manipulation applied to the upper thoracic spine (T1-T4 motion segments) significantly increases cervical rotation ROM and may reduce cervical pain at end range rotation for patients experiencing pain during bilateral cervical rotation.